2007
DOI: 10.1017/s0021932006001568
|View full text |Cite
|
Sign up to set email alerts
|

Additional Confirmation for the Effect of Environmental Light Intensity on the Seasonality of Human Conceptions

Abstract: Causality for the seasonality of human births, which affects populations wordwide, has been a profound mystery for nearly two centuries. Most explanations for seasonality fail because of inconsistent global application. In two previous studies, Cummings (2002, 2003) hypothesized that human reproduction has been responsive to changes in both seasonal environmental light intensity (surface luminosity) and photoperiod. Except at higher latitudes, photoperiod is of secondary importance to that of environmental lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 8 publications
1
18
0
3
Order By: Relevance
“…Although there is no general agreement on the influence of climatic factors (Bronson 2004a), studies outside Italy provide evidence that temperature Myron 1991, 1996;Madrigal 1993;Werschler and Halli 1992), length of photoperiod (Roenneberg andAschoff 1990a, 1990b;Rojansky et al 1992), light intensity (Cummings 2007), and, under specific conditions, the amount of rain (Bailey et al 1992) could account for the seasonal birth profile within communities and populations, even in presence of profound social and economic transformations (Doblhammer et al 2000). For instance, neither the demographic transition, in particular in the United States (Shimura et al 1981), nor the introduction of contraceptives (Shiver 1985) would seem to have introduced significant changes in birth seasonality.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is no general agreement on the influence of climatic factors (Bronson 2004a), studies outside Italy provide evidence that temperature Myron 1991, 1996;Madrigal 1993;Werschler and Halli 1992), length of photoperiod (Roenneberg andAschoff 1990a, 1990b;Rojansky et al 1992), light intensity (Cummings 2007), and, under specific conditions, the amount of rain (Bailey et al 1992) could account for the seasonal birth profile within communities and populations, even in presence of profound social and economic transformations (Doblhammer et al 2000). For instance, neither the demographic transition, in particular in the United States (Shimura et al 1981), nor the introduction of contraceptives (Shiver 1985) would seem to have introduced significant changes in birth seasonality.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent research (Cummings, 2007(Cummings, , 2009) involving sunshine hours and the percentage of possible sunshine confirmed that as the ambient atmosphere changed so did conceptual seasonality change in Germany, The Netherlands, England, Wales, and Scotland. Essentially, spring months became cloudier, autumn months slightly sunnier and peak conceptions slipped into late summer/early autumn.…”
Section: Discussionmentioning
confidence: 90%
“…Sexual behaviour in humans does show seasonal variation. [13][14][15][16][17] This is apparent in many European countries, 13 with peak conception rates occurring in April/May. Conception rates also correlate with increasing exposure to sunlight and with temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Conception rates also correlate with increasing exposure to sunlight and with temperature. 14,15 Further, the frequency of sexual activity, rate of sexually transmitted diseases and the sale of contraceptives are all seasonal, 16 with Carlsen et al 17 demonstrating higher rates of ejaculation during springtime in Danish men. Therefore, seasonal variation in PSA levels may be a reflection of the variation in ejaculation frequency in the studied populations.…”
Section: Discussionmentioning
confidence: 99%